Prospects for using risk scores in polygenic medicine - Cathryn M. Lewis; Evangelos Vassos (Genome Medicine, 2017)
Editorial summary Genome-wide association studies have made strides in identifying common variation associated with disease. The modest effect sizes preclude risk prediction based on single genetic variants, but polygenic risk scores that combine thousands of variants show some predictive ability across a range of complex traits and diseases, including neuropsychiatric disorders. Here, we consider the potential for translation to clinical use.